Modelling and measurements of fibrinogen adsorption on positively charged microspheres - Zeliszewska, P.; Bratek-Skicki, A.; Adamczyk, Z.; Ciesla, M. (Condensed Matter Physics, 2016)
Adsorption of fibrinogen on positively charged microspheres was theoretically and experimentally studied. The structure of monolayers and the maximum coverage were determined by applying the experimental measurements at pH = 3.5 and 9.7 for NaCl concentration in the range of 10⁻³ - 0.15 M. The maximum coverage of fibrinogen on latex particles was precisely determined by the AFM method. Unexpectedly, at pH = 3.5, where both fibrinogen molecule and the latex particles were positively charged, the maximum coverage varied between 0.9 mg m⁻² and 1.1 mg m⁻² for 10⁻² and 0.15 M NaCl, respectively. On the other hand, at pH = 9.7, the maximum coverage of fibrinogen was larger, varying between 1.8 mg m⁻² and 3.4 mg m⁻² for 10⁻² and 0.15 M NaCl, respectively. The experimental results were quantitatively interpreted by the numerical simulations⁻² and 3.4 mg m⁻² for 10⁻² and 0.15 M NaCl, respectively. The experimental results were quantitatively interpreted by the numerical simulations. Теоретично та експериментально дослiджено адсорбцiю фiбриногену на позитивно заряджених мiкросферах. Структура моношарiв i максимальне покриття були визначенi експериментально при pH = 3.5
i 9.7 для концентрацiї NaCl в дiапазонi 10⁻³ − 0.15 M. Максимальне покриття фiбриногену на частинках латексу було визначене прецизiйно методом мiкроскопу атомної сили (AFM). Несподiвано, що при
pH = 3.5, коли i фiбриноген i частинки латексу зарядженi позитивно, максимальне покриття змiнюється
мiж 0.9 мг м⁻²
i 1.1 мг м⁻²
для 10⁻²
i 0.15 M NaCl, вiдповiдно. При pH = 9.7 максимальне покриття фiбриногену є бiльшим i змiнюється вiд 1.8 мг м⁻²
до 3.4 мг м⁻²
для 10⁻²
i 0.15 M NaCl, вiдповiдно. Експериментальнi результати пiдтвердженi чисельним моделюванням.